Exploring the Barriers and Driving Factors in Implementing Building Information Modelling (BIM) in the Malaysian Construction Industry: A Preliminary Study - Zahrizan, Zakaria; Nasly, Mohamed Ali; Ahmad Tarmizi, Haron; Amanda, Marshall-Ponting; Zuhairi, Abd. Hamid (2014)
In Malaysia, Building Information Modelling (BIM) has recently gained attraction from construction players and some of them have applied it to several projects. By utilising the BIM process, the construction players have the opportunity to plan, coordinate and design in an integrated approach. This is one of the many benefits that they could gain and resulting in increased productivity. Despite these benefits, the implementation of BIM in the Malaysian construction industry is still lagging behind Singapore, for instance. Thus, it warrants a study such as the present to determine what are the actual barriers that hamper its implementation and what are the driving factors that could enhance its pace of implementation in the Malaysian construction industry. In this study, a questionnaire survey based on Convenience Sampling Method was carried out to gather the possible barriers and driving factors for BIM implementation among the Malaysian construction players. Additionally, Relative Importance Indices (RII) were used to analyse the data obtained and to identify those barriers and driving factors for the implementation of BIM in this country. Consequently, results of this study revealed that the main barriers for implementing the BIM are: 1) Lack of knowledge about BIM, 2) Reluctance and/or no insistence shown by the Malaysian construction industry players (Clients, Contractors and Consultants alike) on the use or implementation of BIM. The driving factors, on the other hand, that could lead to the speeding up of the implementation of BIM are: 1) Support and enforcing the implementation of BIM by the Government, 2) promote BIM training program and 3) Initiatives of senior management of the related industry players. In conclusion, for successful wide spread application of BIM in Malaysia, a good push from the government alone is far from enough. All other construction industry players mentioned must assume their roles well in promoting the use of BIM in their construction projects.